Assessment of Cost Optimal Solutions for High Performance Multi-family Buildings in Iran. (March 2017) - Alvand, Mohammadhossein; Gholami, Zahra; Ferrara, Maria; Fabrizio, Enrico
Abstract: According to the international benchmarks proposed for the energy demand reduction, the Iranian government, for limiting domestic energy demand growth, has set some energy efficiency policies. In this regard, the present study proposes various solutions to investigate the feasibility of improving the performance of an existing typical multi-family building in Iranian context, to achieve a high performance one with proper cost-optimal levels of energy performance by using the global cost approach defined by EU legislation. Precisely 50 different packages of energy efficiency measures were analyzed in terms of economic and energy performance with consideration on the effects of different envelope thermal insulation, shading system, window types and highly efficient systems in addition to the solar renewable energy source. Then the impact of the selected measures on energy efficiency improvement and global cost were studied and revealed that obtaining high performance building simultaneously with the cost optimal levels can be fulfilled, just when the financial support from the government subsidies exist, otherwise there is still a long way from being economically feasible.